“I am NNEST and I am proud”: Narrative Exploration of ESL Teacher Identity Construction - Biaz Dea Nabilla; Dwi Budidarma Sutrisno (ELE Reviews: English Language Education Reviews, 2023)
The present narrative exploration investigates the factors affecting the language teacher identity negotiation of an international student working as an ESL teacher in an English language program in a research-integrated university. This study uses the qualitative method by drawing on the data from three stages of semi-structured interviews and researchers’ field notes and analyzing it through the perspective of BINF (Bilingual Identity Negotiation Framework). The result reveals the factors influencing the identity negotiation in her trajectory are language competence, educational background, and affirmative discourse at work. These factors led to her investment and participation in the community of practice, where she engaged and included herself in. Overall, this study presents how the ESL teacher identity is linked with the notions of individual agency and public discourse in the community of practice.